Educação, inclusão e políticas públicas: a educação especial no município de Marabá-Pará - COSTA, Vanja Elizabeth Sousa (2006)
This work investigated how happened the implementation of public politic for the Special Education from Marabá - Pará municipal district. Therefore, if done necessary to analyse and to reflect the paper o Municipal Education Secretariat in the execution from that politics, having as focus the school inclusion politic and the process of Municipality of Fundamentals School. The thematic was developed by a qualitaive search about the school inclusion process,for the last decade, in our country, to mark the begin of combat of the Civil Society for stake a claim defended by Federal Constitution 1988, among them guarantee of access and permanence of all in the school. The issue of search that directed this work was verify the relation among the Educational Public Politics for Special Education planned by Federal Government and the implementation from that politics by Education Municipal Secretariat from Marabá - Pará for the school inclusion of students with Special Educational Necessities. The search if developed methodologicaly by a study of case of the school of the Education Municipal net from Marabá. We make use the semi structured interviews and documents as data collect. This documents was submited conted analysis. Begining from our analysis and reflections we testify that introdution of the Special Education in municipal ambit happened by a strong process of municipality had been occured in the year 2000, in Marabá. We stick out that the implementation of the municipality on practice, come suffering many dificulty, among them lack of knowledge of big part of teachers net, in relation of more specific questions showed by majority of deficiences of students them, beyond lack of adequate material structure of schools to attend the students with Educational Specials Necessities matricullated in the common class.